Evaluation of Brain Vascularization via Flow Analysis. An Arterial and Venous Hemodynamic Study with 4D PC-MRI - Gouveia, Margarida Patrício (2023)
Four-dimensional magnetic resonance angiography is a powerful tool for investigating the dynamics of blood flow in arteries, veins, and venous sinuses. When applied to the study of cerebral hemodynamics, this technique can play a crucial role in understanding and diagnosing various brain diseases and neurodegenerative disorders at an early stage. To ensure the clinical applicability of this imaging technique, it is essential to validate its effectiveness. Therefore, the objective of this thesis work was, first and foremost, to study the reproducibility of measurements performed with this technique, namely the measurement of minimum, maximum, and average blood velocities, as well as the cross-sectional area of the internal carotid, middle cerebral, and basilar arteries. The measurements were conducted twice in 7 healthy individuals, between May and June. The results of the reproducibility study were generally satisfactory, although the accuracy of measuring the cross-sectional area of the basilar artery and the middle cerebral artery was compromised. These inaccuracies were attributed to noise resulting from the high value for the velocity encoding employed. Another objective of this thesis was to conduct a comprehensive study of the arterial and venous system in cerebral circulation. To achieve this, various parameters such as Pulsatility Index, Wall Stress, Pressure Drops, and Pulse Wave Velocity were calculated. These parameters were compared with the existing data from the literature, and it was found that they were slightly overestimated. This overestimation was justified by the fact that these parameters are the result of calculations that use velocities, which were already overestimated themselves. The probable cause attributed to the overestimation of velocity was, once again, the high level of noise.